Effect of micro silica on mechanical and durability properties of high volume fly ash recycled aggregate concrete (HVFA-RAC) - Shaikh, Faiz; Kerai, S.; Kerai, S. (Techno-press, 2016)
This paper presents the effect of different micro-silica (MS) contents of 5, 10 and 15 wt.% as partial replacement of cement on mechanical and durability properties of high volume fly ash - recycled aggregate concretes (HVFA-RAC) containing 50% class F fly ash (FA) and 35% recycled coarse aggregate (RCA) as partial replacement of cement and natural coarse aggregate (NCA), respectively. The measured mechanical and durability properties are compressive strength, indirect tensile strength, elastic modulus, drying shrinkage, water sorptivity and hloride permeability. The effects of different curing ages of 7, 28, 56 and 91 days on above properties are also considered in this study. The results show that the addition of MS up to 10% improved the early age (7 days) strength properties of HVFA-RAC, however, at later ages (e.g. 28-91 days) the above mechanical properties are improved for all MS contents. The 5% MS exhibited the best performance among all MS contents for all mechanical properties of HVFA-RAC. In the case of measured durability properties, mix results are obtained, where 10% and 5% MS exhibited the lowest sorptivity and drying shrinkage, respectively at all ages. However, in the case of chloride ion permeability a decreasing trend is observed with increase in MS contents and curing ages. Strong correlations of indirect tensile strength and modulus of elasticity with square root of compressive strength are also observed in HVFA-RAC. Nevertheless, it is established in this study that MS contributes to the sustainability of HVFA-RAC significantly by improving the mechanical and durability properties of concrete containing 50% less cement and 35% less natural coarse aggregates.